Habilidade competitiva e biológica do consórcio beterraba com caupi-hortaliça proveniente de adubação verde e de arranjos espaciais - Carvalho de Morais, Edilson; Suerda Silva de Lima, Jailma; Bezerra Neto, Francisco; Nogueora da Silva, Josimar; Leandro Costa Nunes, Renato; Alves Linhares, Paulo Cássio (Revista Ceres, 2025)
The objective of this work was to evaluate the competitive and biological abilities of the beet and cowpea vegetable intercropping as a function of biomass amounts of roostertree incorporated into the soil and of spatial arrangements. The experimental design was in completely randomized blocks in a 4 × 3 factorial scheme, comprising the combination of four amounts of roostertree biomass (20, 35, 50, and 65 t ha-1 on dry matter) and three spatial arrangements between plant rows of the component crops of the intercropping (2:2, 3:3, and 4:4). The competition indexes were evaluated: actual yield gain or loss, aggressivity, relative crowding coefficient, and competitive ratio. The biological efficiency indexes evaluated were: land equivalent ratios for the system, beet, and cowpea. It was verified that the cowpea vegetable crop obtained higher production gain and a better competition capacity than the beet crop in the established intercropping, and that spatial arrangements did not interfere with the productive performance of the crops. The cowpea vegetable crop was more competitive than the beet in the intercropping system. The highest biological viability of the beet and cowpea vegetable intercropping was obtained in the amount of 65 t ha-1 of roostertree biomass incorporated into the soil. There was no influence of spatial arrangements on the competitive ability and agroeconomic viability of beet and cowpea vegetable intercropping.